Treatment seeking for eating disorders: Results from a nationally representative study. Issue 12 (30th September 2017) - Bohrer, Brittany K.; Carroll, Ian A.; Forbush, Kelsie T.; Chen, Po‐Yi
Abstract: Objective: Eating disorders (EDs) are associated with substantial morbidity and mortality, yet up to 45% of individuals with EDs never receive treatment for their eating‐related problems. This study sought to identify whether comorbidity, suicidality, discrimination, family cohesion, employment status, income, sex, age, marital status, religious belongingness, and ED‐specific variables (body mass index and past‐year ED diagnoses) were associated with treatment seeking in a nationally representative sample of individuals with EDs ( N = 595; 77.8% women; 72.4% ethnic minority). Method: Structural equation modeling was used to identify significant predictors of treatment seeking. Results: In the full sample, age was associated with a greater probability of treatment seeking, and men had a lower probability of seeking treatment. No variables were significant predictors of treatment seeking among individuals in Hispanic or Caucasian subgroups. Discussion: To our knowledge, this was the largest study to characterize predictors of treatment seeking in adults with EDs. Results from this study were consistent with existing literature documenting age and sex differences in treatment seeking among adolescents with an ED. Findings suggest a need for improved ED education and outreach—including greater mental health/ED literacy and decreased stigmatization for patients, providers, and the general public—and additional persuasive public‐health messages to change community knowledge about treatment options for younger persons and men with EDs.